Potensi Situs Arkeologi Gua Hunian Sebagai Daya Tarik Wisata di Pulau Nusa Penida, Bali - Hidayah, Ati Rati (Humanis; Vol 26 No 4 (2022), 2022)
The existence of archaeological sites on the island of Nusa Penida has an important role in the history of human civilization. These sites have significance for science as well as history, but their potential economic significance has not been explored. This paper aims to show the existence of archaeological sites on the island of Nusa Penida and also the economic importance of these sites. One of the potentials that can be developed is as a tourism object that still pays attention to the principles of conservation and cultural resource management (CRM). The research method is in the form of data collection with observation techniques and also literature study, analyzing qualitative data and presenting data in an explanatory descriptive manner. The results showed the potential of archaeological sites as a tourist attraction. Some of the sites that have the most potential to be developed are the Song Gede Site, the Japanese Cave Complex Site, and the Song Toya Pakeh underwater cave site.